Discourse Analysis in the Short Story "Rumah di Dalam Kepala" by Novand Subyanto Maxsonara - Idrus Dama; Hisasmaria Hisasmaria (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This research aims to analyze the discourse in the short story "Rumah di Dalam Kepala" by Novand Subyanto Maxsonara using Critical Discourse Analysis (CDA) approach. The short story portrays the inner journey of the protagonist who carries a house in his head, a symbol of unresolved past trauma. This research examines the discourse structure, social representation, and how social power and ideology are reflected through the language used in the story. The short story addresses issues such as trauma, identity, and psychological healing, as well as depicting the relationship between the individual and society, which is often trapped in social stigma against individuals considered different. The findings of this research show that the symbolism of the house functions as an emotional and psychological space that holds memories and past wounds, while the protagonist's healing process reflects the difficulty of accepting the past and forming a new identity. This analysis also highlights how the short story critiques social norms and emphasizes the importance of providing space for individuals struggling with trauma to heal without stigma.